The first blattid cockroach (Dictyoptera: Blattodea) in Cretaceous amber and the reconsideration of purported Blattidae. (May 2020) - Qiu, Lu Clyde Qiu; Liu, Yu-Chao; Wang, Zong-Qing; Che, Yan-Li
Abstract: Cretaperiplaneta kaonashi Qiu, Che et Wang, gen. et sp. nov. (Blattodea: Blattidae) is described from mid-Cretaceous Burmese amber. This new cockroach resembles the extant genus Periplaneta, with wide apart eyes, smooth pronotum that wider than long, complex venation in tegmina, long but sparse spines on hind margins of femora, tarsomeres with spines, symmetrical tarsal claws, and long, tapered and segmented cerci. However, it is remarkable for its long pubescence on the pronotum and tegmina and the small branches on ScP of tegmen. The taxonomic placements of the previous five Blattidae species found in amber ( Balatronis cretacea Šmídová et Lei, Balatronis libanensis Sendi et Azar, Spinka fussa Vršanský, Šmídová et Barna, Bimodala ohmkuhnlei Šmídová, and Anenev asrev Vršanský, Oružinský, Sendi, Choufani, El-Halabi et Azar) are reconsidered. Spinka fussa and Bimodala ohmkuhnlei are moved to the family Corydiidae; the remaining three are family unsettled species due to their limited taxonomic information.